2009
DOI: 10.1111/j.1469-7610.2009.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological indices of abnormal error‐processing in adolescents with attention deficit hyperactivity disorder (ADHD)

Abstract: The results reveal abnormalities in behavioural and electrophysiological indices of error processing in adolescents with ADHD and suggest that ITC is more sensitive than traditional ERP measures to error-processing abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 49 publications
(68 reference statements)
5
87
2
Order By: Relevance
“…While poor intertrial coherence, as an index of temporal variability of information processing, could reflect reduced myelination (Tamnes et al, 2012) and reduced reliability of neurotransmission (Ford, Roach, Faustman, & Mathalon, 2008;Groom et al, 2010;Winterer et al, 2000), topographic consistency of target P300 could index the stability of the spatial distribution of cortical regions involved in task-related networks (Goldman et al, 2009;Mantini, Corbetta, Perrucci, Romani, & Del Gratta, 2009). In a recent twin study, variability in stimulus eventrelated theta phase from frontal midline cortex was found to be strongly related to both reaction time variability as well as attention deficit hyperactivity disorder, both phenotypically and genetically (McLoughlin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While poor intertrial coherence, as an index of temporal variability of information processing, could reflect reduced myelination (Tamnes et al, 2012) and reduced reliability of neurotransmission (Ford, Roach, Faustman, & Mathalon, 2008;Groom et al, 2010;Winterer et al, 2000), topographic consistency of target P300 could index the stability of the spatial distribution of cortical regions involved in task-related networks (Goldman et al, 2009;Mantini, Corbetta, Perrucci, Romani, & Del Gratta, 2009). In a recent twin study, variability in stimulus eventrelated theta phase from frontal midline cortex was found to be strongly related to both reaction time variability as well as attention deficit hyperactivity disorder, both phenotypically and genetically (McLoughlin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Groom et al (2010) examined intertrial coherence in the context of error monitoring and found that theta ITC was reduced in subjects with ADHD. This is a fact that could contribute to reduced error related negativity in ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2009) examined error processing during a Go/Nogo task in a rare study of children with AD/HDhyp, and reported typical ERN latency and amplitude, but a reduced parietal Pe indicating weaker processing of error recognition. In a traditional Go/Nogo task, adolescents with AD/HDcom have shown no differences in ERN and a trend level effect for Pe (Groom et al, 2010a). Intact error detection, as indicated by ERN (Ne), and deficient error awareness/evaluation, as indicated by reduced Pe, were reported in a study using a demanding Go/Nogo task in children with AD/HD (subtype not specified) (Van De Voorde et al, 2010).…”
Section: Performance Monitoringmentioning
confidence: 93%
“…Alternatively, it has also been suggested that the Pe may correspond to a subsequent, more conscious stage of error detection (Nieuwenhuis et al, 2001), or to some other process associated with error-context updating, similar to P3 activity on correct responses (Leuthold and Sommer, 1999). The ERN and Pe in ADHD children and adults have been reported in several studies (Albrecht et al, 2008;Burgio-Murphy et al, 2007;Groom et al, 2010;McLoughlin et al, 2009;van Meel et al, 2007;Van De Voorde et al, 2010;Wiersema et al, 2005;Wild-Wall et al, 2009;Zhang et al, 2009), using the Go/NoGo or flanker task based on the Eriksen flanker paradigm (Eriksen and Schultz, 1979), but to date no SST study has explored both components of the error processing complex in ADHD children.…”
Section: Introductionmentioning
confidence: 93%